Perancangan LTE Menggunakan Metode Coverage Dimensioning di Kabupaten Kuantan Singingi - Linna Oktaviana Sari; Arif Fauzar; Ery Safrianti; Rahmat Rizal Andhi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
The need for LTE network is not only required by urban communities, but also rural communities. Kuantan Singingi is one of the districts in Riau province, has a lot of potential that can be developed, especially tourism. To develop the potential, Kuantan singingi needs internet network with better signal quality. To meet the needs of high quality internet in Kuantan Singingi then in this research has been done design of LTE internet network in Kuantan Singingi area by using Coverage Dimensioning method with FDD as duplex at 5 MHz bandwidth. The design is done for planning until 2020. The design results have been obtained that Kuantan Singingi requires 54 eNodeBs with cell radius about 6690 meters. In addition, the average RSRP -80dBm obtained with the widest coverage area reaches 99.5%. Then the uplink service area reaches 100% for using 16QAM 3/5 modulation, while downlink service area reaches 71% for QPSK 3/5 modulation.